Tailoring ZnO nanostructures by spray pyrolysis and thermal annealing - Tharsika, T.; Haseeb, A.S. Md. Abdul; Akbar, S.A.; Thanihaichelvan, M. (Elsevier, 2015)
We report a novel synthesis of ZnO nanorods with hexagonal pyramid-like heads by a simple and low cost technique of spray pyrolysis with the help of zinc acetate and tin (IV) chloride pentahydrate precursors. In the present study, the growth of ZnO nanorods is optimized by varying a number of sprays and annealing temperatures in the synthesis process. FESEM analysis reveals that ZnO nanorods are observed when the number of sprays exceeds 150 and film-like structure is observed below 150 sprays. Nanorods are formed when the molar ratio of zinc acetate to tin (IV) chloride pentahydrate in the solution mixture is 3:1. The optimum annealed temperature for the growth of nanorods is determined to be 350 degrees C. The length and diameter of the vertically aligned nanorods are in the range of 1-3 mu m and 80 nm, respectively. XRD diffraction patterns and HRTEM analysis confirm that the ZnO nanorods are single crystals with a preferred growth direction of 0 0 0 1. The effect of various growth parameters including molar ratio of zinc acetate to tin (IV) chloride pentahydrate in the mixture, number of sprays and annealing temperatures on the growth of ZnO nanorods are systematically studied. A plausible growth mechanism for hexagonal pyramidal heads of ZnO nanorods is discussed. These ZnO nanorods with hexagonal pyramid tips have potential application in photovoltaic devices. (C) 2014 Elsevier Ltd and Techna Group S.r.l. All rights reserved.